Free Code-Based Software Music Classes as an Invitation to Fuel Students' Sonic Creativity, Problem Solving, and Community Building - Jorge E Variego (Journal of the Association for Technology in Music Instruction, 2026)
This workshop proposes the integration of free code-based programming software into music classes to expand students' sonic creativity, problem-solving skills, and community-building opportunities.